The detection of growth hormone abuse in sport - Sonksen, P. (1999)
Growth hormone is probably the most anabolic substance yet discovered. It acts directly to stimulate protein synthesis and simultaneously mobilises fat. It acts through a mechanism that is distinct from that of anabolic steroids and its action is complementary to that of testosterone. In adults, growth hormone is probably the most important substance responsible for the development and maintenance of lean body mass. In its absence lean body mass falls and fat accumulates. Growth hormone has been available in unlimited amounts since the late 1980`s and evidence has accumulated showing it to be increasingly abused in sport. The synthetic recombinant growth hormone (rhGH) is the 22k isomer identical to the naturally occurring substance. There are no validated methods of detecting rhGH abuse. Athletes can therefore abuse one of the most anabolic agents known with no risk of detection. GH-2000 was a research project funded by the European Union under their BIOMED 2 research programme with matching funds from the IOC. It`s objective was to develop a methodology for detecting rhGH abuse in time for the Sydney Olympic Games. It ran between January 1996 and 1999. It brought together leading endocrinologists from four European countries (Sweden, Denmark, Italy & UK) with the two European rhGH manufacturers (Novo Nordisk & Pharmacia Upjohn) and the IOC Medical Commission. More than a thousand volunteer elite athletes from around the world participated in the project. The GH-2000 team submitted their Final Report to the European Union and the IOC in January 1999. GH-2000 succeeded in developing a method of detecting rhGH abuse with reasonable sensitivity and very high specificity with a `false positive` rate as low as 1:10,000. Detection of rhGH abuse relies on two methods: The former method is particularly useful in detectingrhGH administration within the last 24h while the latter can detect the use of rhGH as long ago as 14 days before the test. Both methods rely on blood rather than urine tests. GH-200 has thus`cracked the nut` and has shown the detection of growth hormone abuse to be possible. Both tests have very high specificity and adequate sensitivity but before being implemented need further validation to show (amongst other things) that results in other ethnic groups are comparable to those found in the predominantly white Europeans who took part in the first Phase of GH-2000. This new programme of work will be submitted to the IOC for consideration in their recently launched $2 Million research initiative.